2014
DOI: 10.1016/j.jsv.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state self-oscillations and chaotic behavior of a controlled electromechanical device by using the first Lyapunov value and the Melnikov theory

Abstract: In this paper regular and chaotic oscillations in a controlled electromechanical transducer are investigated. The nonlinear control laws are defined by an electric tension excitation and an external force applied to the mobile piece of the transducer.The paper shows that an Andronov-Poincaré-Hopf bifurcation appears as long as adequate parameters are chosen for the nonlinear control laws. The stability of the weak focuses associated to such bifurcation is examined according to the sign of the first Lyapunov va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is well known that the stability of a weak focus depends on the sign of the first Lyapunov value (Guckenheimer et al, 1983;Wiggins, 2000;Pérez_Polo et al, 2014), which is calculated through the normal form of Eqs (24). For this purpose, we obtain the Jordan canonical form of Eq (24) by means of the eigenvector associated to the eigenvalue +iω to obtain the transformation matrix P t , which defines a coordinate transformation as:…”
Section: Analysis Of the Chaotic Behavior Through The First Lyapunov mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the stability of a weak focus depends on the sign of the first Lyapunov value (Guckenheimer et al, 1983;Wiggins, 2000;Pérez_Polo et al, 2014), which is calculated through the normal form of Eqs (24). For this purpose, we obtain the Jordan canonical form of Eq (24) by means of the eigenvector associated to the eigenvalue +iω to obtain the transformation matrix P t , which defines a coordinate transformation as:…”
Section: Analysis Of the Chaotic Behavior Through The First Lyapunov mentioning
confidence: 99%
“…Linearizing the vector field of Eqs (40) along a trajectory and applying the Gram-Smidth orthogonalization method (Pérez-Polo et al, 2014;Lichtenberg et al, 1992;Pérez-Polo et al, 2007), the Lyapunov exponents are obtained as function of time as shown in Fig 6 a). In particular, the whole set of Lyapunov exponents at t = 400 s is given by (Benettin et al, part I-part II 1980):…”
Section: Analysis Of the Chaotic Behavior Through The First Lyapunov mentioning
confidence: 99%
See 1 more Smart Citation